A genetic analysis of Chinese patients with early-onset Parkinson' s disease. (1st November 2022) - Liu, Qi; Jiang, Bin; Zou, Min; Wan, Hui-Juan; Yu, Zi-Wen; Wang, Jing; Xu, Chu-Chuan; Lin, Si-Ning; Zheng, Kun-Mu; Xiao, Nai-An; Bi, Min; Li, Jian-Peng
Highlights: Three novel variants (p.P1043S, p.R1505Q, and p.P266A) in EIF4G1 were identified in our study. Our results reveal a better understanding of the genetic architecture of EOPD (age at onset ≤ 40 years) among the Chinese population. PLA2G6 (13.33 %) was the most common causative gene among our EOPD patients. Abstract: Genetic factors play an important role in early-onset Parkinson's disease (EOPD). The genetic spectrum of patients with EOPD varies widely among different ethnicities, with extensive investigations having been performed in Caucasian populations; however, research in Chinese populations remains limited. In this study, we performed multiplex ligation-dependent probe amplification assay and whole-exome sequencing in 15 unrelated Chinese EOPD patients with age of onset before 40 years. Among them, a patient carried compound heterozygous exon duplications in Parkin (exon 3 duplication and exon 4 duplication) (6.67 %) and two patients carried the homozygous pathogenic variant (p.D331Y) in PLA2G6 (13.33 %). Three novel variants in EIF4G1 (p.P1043S, p.R1505Q, and p.P266A) were identified and classified as uncertain significance. Additionally, a risk variant in GBA (p.L483P) was detected in one patient (6.67 %). PLA2G6 (13.33 %) was the most common causative gene among our EOPD patients. Furthermore, detailed clinical features were presented. Our results broaden the genetic spectrum and clinical phenotypic spectrum of EOPD patients.